Determinan Kepatuhan Ibu Hamil dalam Mengkonsumsi Obat selama Kehamilan - Islah Wahyuni; Linda Suryani (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
The use of drugs during pregnancy aims to improve the health of the mother and fetus. The provision must be adjusted to the needs of the mother and must be under the supervision of health workers. Maternal compliance in taking drugs during pregnancy is influenced by several factors, such as knowledge, attitudes, explanations of how to use drugs from health workers, perceptions and experiences and others. The purpose of the study was to identify the determinants of compliance of pregnant women in consuming drugs during pregnancy. The research sample was 54 respondents who were pregnant women from March to May 2021. The results showed that 29 respondents (53.7%) were obedient in taking drugs during pregnancy, based on the explanation of the majority of health workers, namely 34 people (79.1%), The majority of knowledge is good, namely 35 people (72.9%). Based on the attitude of the majority positive, namely 44 people (68.8%), based on anxiety about drug side effects the majority were 33 people (68.8%), based on the frequency of routine ANC visits (â‰¥4x) namely 32 people (59.2% ). It is hoped that pregnant women can pay attention to the rules and procedures for taking drugs during this pregnancy.